Chronic Aerobic Training at Different Volumes in the Modulation of Macrophage Function and in vivo Infection of BALB/c Mice by Leishmania major - Guimarães, T. T.; Gomes, S. M. R.; Albuquerque, R. A. A. C.; Lima, A. K. C.; Braga, G. F.; Souza, J. B.; Assis, M.; Brito, A. C. S.; Santos, R. F.; Da Silva, T.; Siqueira, L. M.; Ventura, B. D.; et al. (Frontiers in Microbiology, 2021)
Physical inactivity is one of the main causes of chronic diseases; however, strenuous exercise can induce immunosuppression. Several studies suggest that moderate amounts of exercise lead to a Th1 response, favoring the resolution of infections caused by intracellular microorganisms, while high volumes of exercise tend to direct the response to Th2, favoring infection by them. Leishmaniasis is a parasitic disease promoted by parasites of the Leishmania genus, with clinical manifestations that vary according to the species of the parasite and the immune response of the host. The experimental Leishmania major–BALB/C mouse model provides a good model for the resistance (Th1 response) or susceptibility (Th2 response) that determines the progression of this infection. The aim of this study was to evaluate the effect of aerobic training at different volumes on modulation of in vitro macrophage infection by L. major, as well as to assess the effect of high volume (HV) aerobic training on the development of L. major in vivo in BALB/c mice. Uninfected animals were submitted to various exercise volumes: none (SED), light (LV), moderate (MV), high (HV), very high (VHV), and tapering (TAP). The macrophages of these animals were infected by L. major and the LV and MV groups showed a decrease in the infection factor, while the VHV showed an increase in the infection factor, when treated with LPS. The cytokine concentration pattern measured in the supernatants of these macrophages suggested a predominant Th1 response profile in the LV and MV groups, while the Th2 profile predominated in the VHV and TAP groups. Groups of BALB/C mice infected with L. major were subjected to high volume (iHV) or non-periodized high volume (iNPHV) exercise or kept sedentary (iSED). The exercised animals suffered a significant increase in injuries caused by the parasites. The animals in the group submitted to high volume exercise (iHV) showed visceralization of the infection. These data strongly suggest that a very high volume of aerobic training increased the susceptibility of BALB/C mice to L. major infection, while moderate distribution of training loads promoted immunological balance, better controlling the infection by this parasite.